2016
DOI: 10.1186/s13613-016-0183-z
|View full text |Cite
|
Sign up to set email alerts
|

End-inspiratory pause prolongation in acute respiratory distress syndrome patients: effects on gas exchange and mechanics

Abstract: BackgroundEnd-inspiratory pause (EIP) prolongation decreases dead space-to-tidal volume ratio (Vd/Vt) and PaCO2. We do not know the physiological benefits of this approach to improve respiratory system mechanics in acute respiratory distress syndrome (ARDS) patients when mild hypercapnia is of no concern.MethodsThe investigation was conducted in an intensive care unit of a university hospital, and 13 ARDS patients were included. The study was designed in three phases. First phase, baseline measurements were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…Prone positioning may lead to substantial recruitment in many patients with ARDS, which may also reduce dead space and respiratory acidosis. In addition, increasing the duration of inspiration, as with an endinspiratory pause, can decrease Pa CO 2 in small amounts to decrease acidosis from smaller VTs (45,46).…”
Section: Preventing or Reducing Hypercapnia And Acidosis When Using Smentioning
confidence: 99%
“…Prone positioning may lead to substantial recruitment in many patients with ARDS, which may also reduce dead space and respiratory acidosis. In addition, increasing the duration of inspiration, as with an endinspiratory pause, can decrease Pa CO 2 in small amounts to decrease acidosis from smaller VTs (45,46).…”
Section: Preventing or Reducing Hypercapnia And Acidosis When Using Smentioning
confidence: 99%
“…Aguirre- (37). They showed that this decrease in PaCO 2 was correlated with the drop in physiological dead space (37). However, it has also been reported that ventilation with inverted I/E ratio could have deleterious hemodynamic effects (38).…”
Section: How To Protect the Right Ventricle From Hypercapniamentioning
confidence: 98%
“…To avoid such a side effect of too high a RR, Prin et al reported that the use of heated humidifiers significantly decreased the level of PaCO 2 in moderate or severe ARDS, as compared with the use of heat and moisture exchangers (36). Aguirre- (37). They showed that this decrease in PaCO 2 was correlated with the drop in physiological dead space (37).…”
Section: How To Protect the Right Ventricle From Hypercapniamentioning
confidence: 99%
“…In ARDS, this could result in higher levels of intrinsic PEEP, and dynamic airway obstruction and expiratory flow limitation frequently result in air trapping. [15] Our bench setup was designed to see whether we could demonstrate the presence of intrinsic PEEP in the individual patient in a dynamic situation.…”
Section: Intrinsic Peep and Need For Long Inspiratory Timesmentioning
confidence: 99%